2021
DOI: 10.1155/2021/9962007
|View full text |Cite
|
Sign up to set email alerts
|

Panax ginseng C. A. Meyer Phenolic Acid Extract Alleviates Ultraviolet B-Irradiation-Induced Photoaging in a Hairless Mouse Skin Photodamage Model

Abstract: Here, we evaluated the in vivo skin-protective effects of topical applications of Panax ginseng C. A. Meyer extract (PG2) and its phenolic acid- (PA-) based components against UVB-induced skin photoaging. PG2 or PA applied to skin of hairless mice after UVB-irradiation alleviated UVB-induced effects observed in untreated skin, such as increased transepidermal water loss (TEWL), increased epidermal thickness, and decreased stratum corneum water content without affecting body weight. Moreover, PG2 and PA treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…The isolation methods and identification were described. [45][46][47][48] In summary, the plant material of P. ginseng C.A. Meyer was collected from Fusong country of Jilin Province, China.…”
Section: Gs Gpa and Gps Isolationmentioning
confidence: 99%
“…The isolation methods and identification were described. [45][46][47][48] In summary, the plant material of P. ginseng C.A. Meyer was collected from Fusong country of Jilin Province, China.…”
Section: Gs Gpa and Gps Isolationmentioning
confidence: 99%
“…Panax ginseng , one of the most popular TCM plants, is known for its beneficial effects such as anti-inflammatory, improvement of lipid and glucose metabolism, antioxidation, inhibition of cell apoptosis [ 8 ]. Other effects of Panax ginseng are also described in skin such as the decrease of hyperpigmentation [ 9 ], the protection against photodamage [ 10 ] and the repair of skin barrier [ 11 ]. Several of these anti-aging effects are due to the main bioactive compounds of Panax ginseng : the ginsenosides (also named panaxosides).…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] As equine is classified as perissodactyl, it does not have a risk of diseases such as bovine spongiform encephalopathy (BSE) and foot-and-mouth disease; therefore, equine placenta is safe and noninvasive and being expected to use for complementary and alternative medicine (CAM). Regarding previous studies of CAM, Alyasin et al reported that significant efficacy of oral supplementation of whey protein in patients with contact dermatitis to avoid side effects of medication, 12 Li et al evaluated one traditional Chinese medical extract, Panax ginseng phenolic acid extract to protect skin against ultraviolet-B (UVB)-induced photoaging in a mouse experiment, 13 Law et al reviewed a traditional Chinese herbal, dandelion and its applications on skincare and Integrative Medicine. CAM for dermatological diseases and cosmetic purposes has received much interest for its medical use with no side effects, and placenta is one of the important traditional animal materials.…”
mentioning
confidence: 99%